2021
DOI: 10.1111/sdi.12951
|View full text |Cite
|
Sign up to set email alerts
|

Filter life and safety of heparin‐grafted membrane for continuous renal replacement therapy ‐ A randomized controlled trial

Abstract: Acute kidney injury (AKI) is a major complication of critical illness. More than 70% of patients with oliguric AKI and marked azotemia receive renal replacement therapy (RRT). 1 Continuous renal replacement therapy (CRRT) is the preferred option worldwide in critical care, accounting for 80% of all modalities used. 2 However, prolonged extracorporeal circulation is associated with higher risk of filter clotting, which is worsened by the inflammatory and pro-coagulant state in critical illness. 3 Premature cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…The results of our study, which focus on filter life, are comparable and in line with the study by Wong et al 17 who reported similar time(s) and no difference comparing oXiris ® and standard membranes in 20 septic and cardiogenic AKI patients. These comparative findings are also comparable to a clinical study conducted by Shum et al where circuit life using oXiris ® -to modulate sepsis was similar to that of historical controls.…”
Section: Relationship To Previous Studiessupporting
confidence: 92%
“…The results of our study, which focus on filter life, are comparable and in line with the study by Wong et al 17 who reported similar time(s) and no difference comparing oXiris ® and standard membranes in 20 septic and cardiogenic AKI patients. These comparative findings are also comparable to a clinical study conducted by Shum et al where circuit life using oXiris ® -to modulate sepsis was similar to that of historical controls.…”
Section: Relationship To Previous Studiessupporting
confidence: 92%
“…Other adverse events were mainly thrombosis-related adverse events, but no bleeding-related adverse events were seen. Studies have also shown that fixed heparin has no significant systemic anticoagulant or adverse bleeding events ( 55 ). This also suggests that we should regulate anticoagulation according to the condition of oXiris treatment to reduce activation of the coagulation system and the consumption of coagulation factors and platelets.…”
Section: Discussionmentioning
confidence: 99%
“…The preliminary observation made in this study certainly deserves further and deeper experimental insights. In a single-center, prospective, open-label, pilot randomized controlled study using a crossover design, Wong et al [9] failed to demonstrate that heparin coating alone can reduce membrane fouling in critically ill patients. In fact, treatment prescription and specific patients' characteristics may critically contribute to membrane fouling, independently from membrane biocompatibility.…”
Section: Discussionmentioning
confidence: 99%
“…The oXiris membrane (Baxter, Deerfield, IL, USA) is a biocompatible high-flux hemodiafilter combining diffusive and convective clearances, used to support renal function and to remove circulating cytokines and endotoxins [8]. More specifically, the heparin-coated layer of the oXiris membrane limits the activation of the coagulation cascade, which is often overly activated in patients with severe hyper inflammation (e.g., critically ill septic patients [9]).…”
Section: Introductionmentioning
confidence: 99%